Table of Content - -, (Journal of Islamic Sciences, 2025)
Table of Content:1. Love in the Islamic ReligionDr. Mohammed Remedan Yusuf2. The effects of the phenomenon of extremism on intellectual securityDr. Majed Marzoug Al-Harbi3. Abortion between Islamic provisions and a criminal crimeAsst-lecturer \ Maad Dhaeer Naeem4. Smoke and Vapor of Najāsah Between Fiqh and Chemistry: An Analytical Jurisprudential StudyDr. Musatafa Muhammad Karakira
Keywords: Journal of Islamic Sciences